Implementasi Kebijakan Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Kota Semarang - Alif Nurkhoiri, Muhammad; Rina Herawati, Augustin; Afrizal, Teuku (Journal of Public Policy and Management Review, 2024)
This research evaluates the implementation of the Complete Systematic Land Registration (PTSL) policy in Semarang City, designated for the Complete City program in 2024, using the implementation model by Van Meter and Van Horn. The focus is on PTSL activities and the factors affecting its implementation. The findings indicate that the Semarang City Land Office successfully executed the PTSL policy, despite challenges related to human resources and infrastructure. Strategies such as forming special teams (Physical, Legal, and Administrative Task Forces) and empowering local communities as Data Collectors, alongside efficient information systems, were adopted. Stakeholder participation and transparency in the registration process are crucial for effective policy implementation. Regular evaluations, both monthly and annually, are necessary to ensure long-term target achievement and to address emerging issues. The study found that, despite obstacles like insufficient human resources and coordination among stakeholders, the strategies employed yielded positive results with a high success rate in land certification completion. Recommendations include enhancing human resource training to ensure adequate skills and improving coordination by involving community representatives from neighborhood units (RT) and community units (RW) as facilitators.